(untitled) (MAUSAM, 1990)
In this paper, considering total seasonal rainfall of June through September as well as its time distribution, an index has been evolved for identifying a year as hydrologically flood/drought in different parts of India. After giving a margin of ± 25% to the mean index value for normal years, frequencies of flood/drought year have been calculated. In general, frequencies of both hydrological flood and drought years are more in low rainfall areas as compared to high rainfall areas. They compared quite closely with the frequencies of meteorological excessive and deficient rainfall years respectively. But the categorization of some individual years is found to differ between meteorological and hydrological points of view. The nature of these differences is, however, not uniform at all the stations.